Preventing bullying through islamic educational values: A theoretical and practical perspective - Muchammad Iqbal Chailani; Khamim Saifuddin; Ahmad Aji Pangestu; Ludfiyana Munawarotul hasanah; Farach Feby Febyola; Elin Agustyana; Ike Styaningrum; Husna Nashihin (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2023)
The phenomenon of bullying in educational environments is increasingly alarming due to its adverse effects on students' psychological and social development. This study aims to explore the role of Islamic Religious Education values in preventing bullying behavior through both theoretical and practical approaches. A descriptive qualitative method was employed, utilizing literature studies and contextual observations within school settings. The findings indicate that Islamic values such as compassion (rahmah), justice (‘adl), and brotherhood (ukhuwah) hold transformative potential in shaping student character and fostering a friendly school culture. The implementation of these values through teacher role models, curriculum integration, and experience-based approaches has proven effective in reducing bullying practices. Islamic Religious Education must be continually reinforced as a foundation for character education grounded in universal humanistic values. This is an open-access article under the CC–BY-SA license.